Determination of Flow Rate Coefficient for Compound Weir: Trapezoidal-Rectangular Shape - Zamri, Nur Aisyah Fatihah; Zarina Md Ali (Journal of Advancement in Environmental Solution and Resource Recovery, 2026)
Effective water resource management is vital for sustainable development and environmental resilience, with hydraulic structures such as compound weirs playing a key role in flow regulation. This study investigates the discharge coefficient, Cd and relationships between flow rate (Q), water height (H), and Cd of trapezoidal-rectangular compound weirs.  Nine weir models with varying geometric configurations were tested to through controlled laboratory experiments at the Fluid Mechanics Laboratory at Universiti Tun Hussein Onn Malaysia.  The Bernoulli equation was applied as the primary tool to compute theoretical flow rates and discharge coefficients. The findings reveal significant variations in Cd values where coefficients of determination (R²) ranged from 0.95 to 0.99. It indicates strong relationships and high data reliability. For weirs with L₁ = 0.03 m and L₂ = 0.06 m, the average Cd values were between 0.54 and 0.63 for trapezoidal angles of 40°, 25°, and 15°, respectively. In contrast, weirs with L₁ = 0.05 m and L₂ = 0.08 m showed lower Cd values of 0.53, 0.51, and 0.47 for the same angles. This study enhances understanding of hydraulic behaviour in compound weirs and facilitates optimized design, providing significant insights for flood control, irrigation, and sustainable water management.